Assessing the effects of subject motion on T(2) relaxation under spin tagging (TRUST) cerebral oxygenation measurements using volume navigators - Stout, Jeffrey N. (Magn Reson Med, 2017)
PURPOSE: Subject motion may cause errors in estimates of blood T(2) when using the T(2)-relaxation under spin tagging (TRUST) technique on non-compliant subjects like neonates. By incorporating three-dimensional volume navigators (vNavs) into the TRUST pulse sequence, independent measurements of motion during scanning permit evaluation of these errors. METHODS: The effects of integrated vNavs on TRUST-based T(2) estimates were evaluated using simulations and in vivo subject data. Two subjects were scanned with the TRUST+vNav sequence during prescribed movements. Mean motion scores were derived from vNavs and TRUST images, along with a metric of exponential fit quality. Regression analysis was performed between T(2) estimates and mean motion scores. Also, motion scores were determined from independent neonatal scans. RESULTS: vNavs negligibly affected venous blood T(2) estimates and better detected subject motion than fit quality metrics. Regression analysis showed that T(2) is biased upwards by 4.1 ms per 1 mm of mean motion score. During neonatal scans, mean motion scores of 0.6–2.0 mm were detected. CONCLUSION: Motion during TRUST causes an overestimate of T(2), which suggests a cautious approach when comparing TRUST-based cerebral oxygenation measurements of noncompliant subjects.